La flexibilidad y su importancia en la práctica de yoga en estudiantes de bachillerato - Tierra Iza, Jhon Jairo (2023)
The theme developed in the present research is "Flexibility and its importance in the yoga practice in high school students." This study aims to determine the influence of yoga practice on flexibility in students in the third year of high school of Parallel A and B from the José Ramón Zambrano Educational Unit. The research addressed a cross-sectional study through a qualitative and quantitative approach, whose analysis served to recognize the main effects of yoga on young students. Due to temporary confinement because of covid 19, people did not perform physical activity, which affected joint flexibility. A sample of 47 high school students was considered, 30 male and 17 female, respectively. Physical activity levels and mood were analyzed. The applied instrument was the Wells and Dillon Test (1952). For the statistical analysis, the Excel statistical program was used. It was defined that most of the students are at an average and good level concerning their measurements in the flexibility test. Therefore, the proposal of a yoga program for 3rd- year high school students was proposed to improve flexibility and motivate the practice of it as a support tool in the educational area. Various postures and activities related to yoga are proposed to intervene in the back area, maintaining the health of the body